2018
DOI: 10.1264/jsme2.me17138
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Insights into Endofungal Lifestyles of Two Bacterial Endosymbionts, <i>Mycoavidus cysteinexigens</i> and <i>Burkholderia rhizoxinica</i>

Abstract: Endohyphal bacteria (EHB), dwelling within fungal hyphae, markedly affect the growth and metabolic potential of their hosts. To date, two EHB belonging to the family Burkholderiaceae have been isolated and characterized as new taxa, Burkholderia rhizoxinica (HKI 454T) and Mycoavidus cysteinexigens (B1-EBT), in Japan. Metagenome sequencing was recently reported for Mortierella elongata AG77 together with its endosymbiont M. cysteinexigens (Mc-AG77) from a soil/litter sample in the USA. In the present study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 67 publications
(100 reference statements)
2
31
1
Order By: Relevance
“…The microbiome of Inocybe terrigena (scaly fibre head) fruiting-bodies also includes bacteria showing symbiotic functions, regardless of habitat conditions (Bahram et al, 2018). Among the symbiotic bacteria reported by the cited authors to inhabit the I. terrigena basidiomes: the genus Pseudomonas is, as already reported above, associated with mushroom fructification (Colauto et al, 2016), Pedobacter species are noted for carrying a large number and variety of antimicrobial resistance genes (Viana et al 2018), and have been reported to detoxify tolaasin produced by the mushroom pathogen Pseudomonas tolaasii (Tsukamoto et al, 2002) and Burkholderia members have been reported to enter into beneficial interactions with mycorrhizal and other fungi, including intracellular symbioses (Frey-Klett et al, 2011;Sharmin et al 2018). Table 1 compiles recent literature describing bacteria associated with the mycelium and fruit bodies, including the techniques employed to characterize the microbiome, methods implemented and role reported.…”
Section: The Mushroom Holobiont: Mycelium and Fruit Bodymentioning
confidence: 66%
See 1 more Smart Citation
“…The microbiome of Inocybe terrigena (scaly fibre head) fruiting-bodies also includes bacteria showing symbiotic functions, regardless of habitat conditions (Bahram et al, 2018). Among the symbiotic bacteria reported by the cited authors to inhabit the I. terrigena basidiomes: the genus Pseudomonas is, as already reported above, associated with mushroom fructification (Colauto et al, 2016), Pedobacter species are noted for carrying a large number and variety of antimicrobial resistance genes (Viana et al 2018), and have been reported to detoxify tolaasin produced by the mushroom pathogen Pseudomonas tolaasii (Tsukamoto et al, 2002) and Burkholderia members have been reported to enter into beneficial interactions with mycorrhizal and other fungi, including intracellular symbioses (Frey-Klett et al, 2011;Sharmin et al 2018). Table 1 compiles recent literature describing bacteria associated with the mycelium and fruit bodies, including the techniques employed to characterize the microbiome, methods implemented and role reported.…”
Section: The Mushroom Holobiont: Mycelium and Fruit Bodymentioning
confidence: 66%
“…), and have been reported to detoxify tolaasin produced by the mushroom pathogen Pseudomonas tolaasii (Tsukamoto et al ., ) and Burkholderia members have been reported to enter into beneficial interactions with mycorrhizal and other fungi, including intracellular symbioses (Frey‐Klett et al ., ; Sharmin et al . ). Table compiles recent literature describing bacteria associated with the mycelium and fruit bodies, including the techniques employed to characterize the microbiome, methods implemented and role reported.…”
Section: The Mushroom Holobiont: Mycelium and Fruit Bodymentioning
confidence: 97%
“…Fungi harbor a wide diversity of bacterial endosymbionts that are specifically adapted to colonize their fungal hosts and significantly influence host-relevant fungal phenotypes, including metabolism, cell wall organization, development, and plant host colonization 35,58,59,81,90,94,96-106 . Additionally, endobacteria are a source of potent mycotoxins that can influence fungal pathogenesis in plants and insects 59,60,81,90,107,108 . New patient populations are now susceptible to a broadening diversity of basal saprobic fungi, which are a major emerging cause of clinically important superficial and disseminated fungal infections 18,109 .…”
Section: Resultsmentioning
confidence: 99%
“…BRE were generally found in hyphae and asexual spores (Lumini et al, 2007;Sato et al, 2010;Ohshima et al, 2016;Mondo et al, 2017;Takashima et al, 2018a) as well as in sexual spores (Mondo et al, 2017). The host nutrient dependence of BRE due to genome reductions was suggested by genomic studies (Ghignone et al, 2012;Fujimura et al, 2014;Uehling et al, 2017;Sharmin et al, 2018). However, limited information is currently available on the effects of BRE on their fungal hosts.…”
mentioning
confidence: 99%